Ewing sarcoma of bones: pathomorphological features, immunohistochemical and differential diagnosis - VOLOS, L. I.; DUDASH, A. P.; BONDARCHUK, N. B. (Experimental and Clinical Physiology and Biochemistry, 2025)
Ewing sarcoma is a high-grade, small round cell tumour of bones in children and young adults, prone to rapid metastasis and recurrence. The aim of the study was to establish the morphological features of the «classic variant» of Ewing sarcoma, to conduct immunohistochemical verification and differential diagnosis. Methods. Histological and immunohistochemical studies of diagnostic bone biopsies and postoperative material obtained from 7 patients with a clinical diagnosis of Ewing's sarcoma were performed in compliance with the basic provisions of the Rules for Ethical Principles for Scientific Medical Research Involving Human Subjects. For the diagnosis of Ewing's sarcoma, an immunohistochemical panel was used, including monoclonal antibodies to CD99/MIC2, FLI1, NKX2.2, CD45/T200/LCA Ab-2, Pan-CC, Desmin Ab-1, Myogenin, TdT, the study was performed in accordance with the manufacturer's protocol with the necessary controls. Histological evaluation was performed using a Leica DM750 universal optical microscope (Leica Microsystems GmbH). Results. Diagnosis of Ewing sarcoma is difficult, and immunohistochemical methods using antibodies play an important role. Tumor cells of Ewing sarcoma are positive for CD99 (membranous and diffuse), NKX2.2 (nuclear and diffuse), FLI1 (nuclear and diffuse), while they are negative for cytokeratin cocktail, desmin, myogenin, TdT, and CD45, confirming the diagnosis of Ewing sarcoma. Conclusions. During histological examination of Ewing sarcoma, it is necessary to conduct differential diagnosis using a panel of immunohistochemical markers with other small round cell malignant neoplasias that are similar in cytomorphological features.